pH‐Responsive Torpedo‐Like Persistent Luminescence Nanoparticles for Autofluorescence‐Free Biosensing and High‐Level Information Encryption - Li, Juan; Huang, Xiaolin; Zhao, Xu; Chen, Li‐Jian; Yan, Xiu‐Ping (Angewandte Chemie International Edition, 2021)
Persistent luminescent nanoparticles (PLNPs) with intrinsic stimuli‐responsive properties are desirable because of no autofluorescence background and natural responsive luminescence. However, the stimuli‐responsive features of pure PLNPs have been unexplored. Here we show a facile one‐pot hydrothermal synthesis of green‐emitting Zn2GeO4:Mn2+,Pr3+ nanoparticles (ZGMP) with regular shape, uniform size and good afterglow luminescent performance. We also report the pH stimuli‐responsive luminescent behavior of ZGMP and its possible mechanism. Taking the intriguing feature of pH responsive persistent luminescence, we explore ZGMP as autofluorescence‐free probes to achieve stimuli‐activated signal switch for biosensing by integrating enzyme catalysis reaction mediated pH modulation. The pH‐responsive persistent luminescence also makes ZGMP promising for high‐level information encryption. Uniformly torpedo‐shaped green‐emitting Zn2GeO4: Mn2+, Pr3+ nanoparticles with good persistent luminescence performance were synthesized by a simple hydrothermal method. The pH‐responsive persistent luminescence of ZGMP was found and explored for autofluorescence‐free biosensing and high‐level information encryption.